If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6b + 28 = 9b + -2 Reorder the terms: 28 + -6b = 9b + -2 Reorder the terms: 28 + -6b = -2 + 9b Solving 28 + -6b = -2 + 9b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9b' to each side of the equation. 28 + -6b + -9b = -2 + 9b + -9b Combine like terms: -6b + -9b = -15b 28 + -15b = -2 + 9b + -9b Combine like terms: 9b + -9b = 0 28 + -15b = -2 + 0 28 + -15b = -2 Add '-28' to each side of the equation. 28 + -28 + -15b = -2 + -28 Combine like terms: 28 + -28 = 0 0 + -15b = -2 + -28 -15b = -2 + -28 Combine like terms: -2 + -28 = -30 -15b = -30 Divide each side by '-15'. b = 2 Simplifying b = 2
| 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 |